Post-Glacial Isostatic Adjustment and Global Warming in Subarctic Canada: Implications for Islands of the James Bay Region - Tsuji, Leonard J.S.; Gomez, Natalya; Mitrovica, Jerry X.; Kendall, Roblyn (ARCTIC, 2009)
When Rupert’s Land and the North-Western Territory became a part of Canada as the Northwest Territories in 1870, the islands of James Bay were included within the new territorial boundaries. These same islands became a part of Nunavut in 1999, when the new territory was created from the eastern region of the Northwest Territories. Although the James Bay islands remain part of Nunavut, the western James Bay Cree assert that the western James Bay islands, including Akimiski Island, were part of the Cree traditional territory and that these islands have never been surrendered through treaty. This land-claim issue is further complicated by the fact that glacial isostatic adjustment (GIA) is occurring in the James Bay region and that the islands of James Bay may one day become part of mainland Ontario or Quebec. We used numerical models of the GIA process to predict how shorelines in James Bay will migrate over the next 1000 years as a result of post-glacial sea-level changes. These predictions, which were augmented by an additional contribution associated with sea-level rise due to global warming, were used to determine whether the islands in James Bay will ever become part of the mainland. The predictions for the islands are sensitive to the two primary inputs into the GIA predictions, namely the models for the geometry of the ancient Laurentide ice sheet and the viscoelastic structure adopted for the solid earth, as well as to the amplitude of the projected global warming signal. Nevertheless, it was found that many of the smaller and larger islands of James Bay will likely join the mainland of either Ontario or Quebec. For example, using a global warming scenario of 1.8 mm sea-level rise per year, a plausible range of GIA models suggests that the Strutton Islands and Cape Hope Islands will join mainland Quebec in ~400 years or more, while Akimiski Island will take at least ~700 years to join mainland Ontario. Using the same GIA models, but incorporating the upper boundary of global warming scenarios of 5.9 mm ...